Arthroscopic-Controlled Reduction of Hill-Sachs Lesions: Treatment Option for Off-Track Lesions in Young Patients? - Malte Ohlmeier, M.D.; Adrian Schlichter, M.D.; Richard Stange, M.D. (Arthroscopy Techniques)
Large Hill-Sachs lesions (HSL) are currently treated via a remplissage procedure. Although the good stabilizing properties of this surgery are apparent, there are some disadvantages in terms of the functional outcome. In the following Technical Note, we present a method of arthroscopic-controlled reduction of HSL for anatomical restoration of the humeral head without functional limitations. For HSL reduction, we place a 1.6-mm K-wire in the central lesion under arthroscopic and fluoroscopic control from posterior to anterior in lateral drilling direction. Then, a 7-mm cannulated drill is used for preparing the reduction canal. Afterward, the HSL is reduced via bone tamp, also under arthroscopic and fluoroscopic control. No bone substitution material is used to fill the canal; only a standard wound closure is performed. Arthroscopic-controlled reduction of impacted humeral head fractures seems to be a possible and relatively easy way to perform an anatomical restoration of HSLs. Because the exact location of HSLs can vary slightly, the exact surgical setting might be slightly different each time. Biomechanical studies already show similar stabilizing properties of this procedure compared with established techniques but without losing external rotation. Further studies need to review the potential rate of humeral head necrosis or secondary loss of reduction.